2015
DOI: 10.1016/j.jdds.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Serum prolactin levels in dermatological diseases: A case–control study

Abstract: Background: Recent lines of evidence suggest that prolactin (PRL) as a neurohormone may play a role in the activity of psoriasis and some other immune-mediated diseases. Our aim was to evaluate the correlation between serum PRL levels and severity of psoriasis, vitiligo and alopecia areata.Patients and methods: We performed a case-control study on 100 subjects: 75 patients; suffering from psoriasis, vitiligo and alopecia areata; 25 patients in each group and 25 age-and sex-matched healthy controls.Results: Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
1
6
1
Order By: Relevance
“…The positive relationship between mean prolactin concentration and the number of GI events is an interesting finding that should be explored in more detail. Studies in humans have also revealed a role of prolactin in the pathogenesis of certain skin pathologies [105, 106], with significantly higher serum prolactin in patients with psoriasis, vitiligo and alopecia areata, when compared to controls [107]. The phenomenon of hyperprolactinemia has previously been associated with reproductive dysfunction in African elephants living in North American zoos [108, 109] and these results suggest there may be other impacts on health, which should be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…The positive relationship between mean prolactin concentration and the number of GI events is an interesting finding that should be explored in more detail. Studies in humans have also revealed a role of prolactin in the pathogenesis of certain skin pathologies [105, 106], with significantly higher serum prolactin in patients with psoriasis, vitiligo and alopecia areata, when compared to controls [107]. The phenomenon of hyperprolactinemia has previously been associated with reproductive dysfunction in African elephants living in North American zoos [108, 109] and these results suggest there may be other impacts on health, which should be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 10 ] Accordingly, both studies denied a possible role of prolactin in the pathogenesis of AA, something we could not state owing to the further studying of the prolactin receptor. On the contrary, two other studies documented a significantly elevated level of serum prolactin in AA patients compared to controls,[ 11 12 ] and that serum prolactin level was significantly correlated with disease severity. [ 11 ]…”
Section: Discussionmentioning
confidence: 93%
“…On the contrary, two other studies documented a significantly elevated level of serum prolactin in AA patients compared to controls,[ 11 12 ] and that serum prolactin level was significantly correlated with disease severity. [ 11 ]…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…PRL appears to have extra capacities in skin science and hair follicle development also. This notable chemical has been acknowledged in a few articles as an immunostimulatory factor in immune system issues like psoriasis and lupus erythematosus [3].…”
Section: Introductionmentioning
confidence: 99%